Tax Culture: Perspectives from an African State - Atuguba, Raymond A. (American Journal of Trade and Policy, 2021)
Universally, Tax Culture is not a very common topic but it is critical to administrative governance and economic development. This article argues that the Tax Culture of any milieu is an assemblage of various indices and criteria. These include the history of taxation; tax laws; tax information; tax education; tax revenue mobilization; tax system transparency; tax delinquency; tax dispute resolution; and taxpayer satisfaction. The article sheds light on these instrumental wheels of the Tax Culture of Ghana by providing the research results of field surveys conducted a decade and a half ago. Though dated, any observer of the Tax Culture of Ghana, and indeed of much of Africa and the Global South, will realize that little has since changed. In some instances, the article provides more up-to-date evidence beyond the 2005 data. The article goes beyond an assessment of the Tax Culture of Ghana and articulates recommendations for improving the same. Additionally, it attempts to interconnect issues of Taxation, Good Governance, and Legal Pluralism. Although popular themes in public discourse in Africa today, these concepts are often spoken of in different thematic spheres other than taxation. The article links these themes in practical and concrete ways to taxation, cast in the light of historical institutionalism – an examination of the institutions of taxation, governance, and traditional authority as they interacted through time.